Evaluation of Roadway Level of Service for Pedestrian Movement: A Case Study on Katiadi Paurashava of Kishoreganj District (Journal of Bangladesh Institute of Planners, 2017)
The Level of Service (LOS) has proved to be a practical and significant “quality of service” indicator for transportation facilities and is being widely used in the transportation and planning fields. The LOS rates these facilities’ traffic operating conditions through the indicators (ordered from best to worst conditions): A, B, C, D, E and F. This LOS rating has its base on scientific measures of efficiency and on road users’ perceptions. On the whole, these measures define a LOS based on acceptable traffic operating conditions for the road user. In short, Level of service is commonly used to assess the operational quality of transportation facilities in the roadway as well as roadside conditions. The primary objective of this study is to determine the Level of Service (LOS) of the primary, secondary and access roads for pedestrian movement in the study area. This study uses the average space occupied by the pedestrian as the main performance indicator for determining the pedestrian LOS. Pedestrian perception based LOS ratings are also evaluated about various roadway characteristics (e.g. traffic safety, sidewalk/road shoulder condition, road surface condition, pedestrian crossings/intersections, street lighting system etc.) for different types of roads.JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 71-87